PENGARUH KOMUNIKASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PADA PENGURUS UAM FAKULTAS EKONOMI DAN BISNIS - Mifthaul Hanan; Hadi Sunaryo; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT This study aims to determine the effect of communication and leadership style on the performance of the UAM faculty of economics and business. The variables used in this study are performance variables (dependent variables), while the independent variables are communication and leadership style. The results of this study partially concluded that there was no influence between communication variables on the performance of the management and there was an influence between leadership style variables on the performance of the management. Key words: Performance, communication, leadership style.